Oral Sucrose Versus Breastfeeding in Managing Infants' Immunization-Related Pain: A Randomized Controlled Trial. Issue 2 (March 2019) - Gad, Rasha F.; Dowling, Donna A.; Abusaad, Fawzia E.; Bassiouny, Mohamed R.; Abd El Aziz, Magda A.
ABSTRACT: Background: Treating pain during immunization should be a part of pediatric primary healthcare around the world, as untreated pain in children has short- and long-term consequences. Few studies of pharmacologic and nonpharmacologic methods of pain relief during immunization have been conducted in low- and middle-income countries. Finding pain-mitigating interventions that are low-cost, effective, and feasible across all settings, including with low-resourced settings could improve primary healthcare. Purpose: To evaluate the effectiveness of oral sucrose versus breastfeeding as methods of pain management during immunization of infants through 6 months of age. Methods: A randomized controlled experimental design was used; 120 infants were randomly assigned to control, sucrose, or breastfeeding groups. Data were collected in an Egyptian primary health center. Outcome measures including pain (as per the FLACC pain scale), crying time, and heart rate were measured at three time points. Results: There were significant differences in pain scores and crying duration during and after immunization ( p < .001) for the breastfeeding group compared with the sucrose and control groups. Implications for Practice: Health staff and parents need education and support in use of breastfeeding for pain management during immunization. More studies are needed to evaluate effectiveness of breastfeeding versus other pain management methods for managing infants' immunization-related pain. Abstract : Immunization is one of the most painful procedures in infancy and causes anxiety and distress for infants and their parents. In this randomized controlled trial, during immunization, 120 babies up to six months old were randomized to breastfeeding, oral sucrose, or the usual comforting measures. Measures of pain were lower in the breastfeeding group. Breastfeeding during immunization should be offered to women and their babies routinely as a pain avoidance procedure.